Sustainable Mosque Designs from the Perspectives of Social Inclusion: Comparisons of Four Mosques in Kuala Lumpur, Malaysia - Jamail, M I; Samsudin, I L; Rasdi, M T M; Sabil, A; Yola, L (International Journal of Sustainable Construction Engineering and Technology, 2023)
One of the major conflicts continuously occurring in Malaysia is the issue of race and religious relationships. Today, houses of worship in Malaysia have always been seen as isolated entities that can add to race relations and nation-building conflicts. This issue has led to the planning of houses of worship as nation-building elements in forging social inclusion among the different religious buildings of other faiths. Therefore, this research aims to evaluate mosques' social inclusion characteristics, which can contribute to the more extensive framing of Malaysian planning policy on the sustainable design of houses of worship. To reflect the ideal of SDG 11, Sustainable cities and communities and SDG 16, Peace, justice and strong institutions, it is essential to identify social inclusivity as one of the primary design approaches for any Islamic institutions and mosques designs. Should the mosques be part of the nation-building entities and not just community centres for each faith? This research covers selected case studies mainly in Kuala Lumpur, representing the city with the most educated and diverse multi-faith context. Four significant mosques were selected and studied through observations and interviews data collection approach. The research findings indicate that elements such as scale, massing, permeability, visibility, territoriality, and iconic imagery are essential to design criteria for mosques. Significantly, this research provides suggestions and guidelines for designers and committee leaders of all religions in Malaysia to re-look at the activities and planning aspects of their houses of worship. Furthermore, it helps to promote inclusive elements such as social interaction, tolerance, and understanding of different religious beliefs. Hence, accepting these multi-faith centres will create a more integrated, harmonious and sustainable community.